Historical Dictionary of NATO and Other International Security Organizations. - Rimanelli, Marco (Historical dictionaries of international organizations series., 2008)
The Historical Dictionary of NATO and Other International Security Organizations covers the Atlantic Alliance's origins, structure and organization through a list of acronyms and abbreviations, a chronology, an introductory essay, a bibliography, and over 1,000 cross-referenced dictionary entries on its Secretaries-Generals, its Supreme Allied Commanders-Europe, plus all affiliated organizations created to enhance NATO's reach in a broader Euro-Atlantic security architecture (e.g. North Atlantic Consultative Council, Euro-Atlantic Partnership Council, NATO-Russia Charter; NATO-Ukraine Charter.